'Far from the views of decision-makers': podoconiosis instruction at medical schools across endemic countries in Africa. (9th November 2020) - Fowler, Kelly; Wampande, Lilian Nantume; Gebreselassie, Agazi; Bayisenge, Ursin; Uwase, Chany; de Oliveira, Adilson; Schurer, Janna M
Abstract: Background: Podoconiosis is a neglected tropical disease that causes significant physical, emotional and financial suffering, especially among impoverished rural farmers. Sufficient physician training is integral to optimizing patient outcomes through timely diagnosis and appropriate management. Therefore we sought to characterize podoconiosis instruction offered to medical students in endemic African countries. Methods: We invited faculty from 170 medical schools in all podoconiosis-endemic African countries to provide information about podoconiosis inclusion in medical curricula. Surveys were available in French and English and captured podoconiosis knowledge, quantity/quality of instruction, ranking of importance relative to other diseases and barriers for improvement. Respondents voluntarily shared responses online or by telephone. Results: Study participants provided information about curricula at 97 medical schools across 14 countries. In total, 42.6% of schools across nine countries offered podoconiosis-specific instruction; most respondents felt that the quality (60.4%) and quantity (61.5%) of instruction was insufficient. Common barriers to sufficient training included exclusion from government curricula, prioritization according to caseload and scarce epidemiological data. Conclusions: Our study demonstrates widespread neglect in podoconiosis training for physicians in endemic countries. Government support is needed to ensure curricula match the needs of health workers practicing in rural, low-income regions.